Indonesian Life Expectancy: Role of Health Infrastructure and Socio-Economic Status - Endri Kristanto; Akhmad Daerobi; Bhimo Rizky Samudro (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
The purpose of this study is to analyze the role of health infrastructure and public socio-economic status on life expectancy in Indonesia. Health infrastructure indicators are health personnel, health facilities, and health insurance. Meanwhile, socio-economics indicators are dependency ratio, income inequality, and poverty. The models are estimated using a panel data set for 34 provinces in Indonesia from 2010 to 2016. This research is using a fixed-effect panel data approach. Empirical results show that health personnel and health insurance have a positive relationship with life expectancy. Dependency ratios and poverty also show a negative relationship with life expectancy. On the other hand, the availability of health facilities and income inequality have a weak relationship with life expectancy. This empirical examination result will help Indonesian governments to improve several aspects in order to increase life expectancy in Indonesia